Isolation and screening of an electrochemically active strain Bacillus cereus sp. WL027 using phenol as fuel and preliminary study on its mechanism of electricity production - WANG Lili; GUO Wei; FU Chunna; YAN Hong (浙江大学学报. 农业与生命科学版)
Microbial fuel cell (MFC) is an economic and effective way for wastewater treatment, which enables not only degradation of phenol but also conversion of biomass energy into electricity. Selection and breeding of electricigens from anode of a microbial fuel cell is the premise and foundation of MFC research; meanwhile, the problem of low energy efficiency can also be solved. Electronic delivery mechanisms of electricigens included biofilm mechanism and electron shuttle mechanism. Biofilm mechanism refers to the electricigens being attached to the electrode surface and then use cytochrome C or “nanowires” to transfer intracellular electrons to the electrode through the biofilm. Electronic shuttle mechanism concerns the use of a redox mediator to transfer electrons between the cell and the electrode. Currently, most Gram-negative bacteria with cell walls rich in cytochrome C, have been found to use cytochrome C to transfer electrons, such as Geobacter sulfurreducens, Aeromonas hydrophila and Rhodoferax ferrireducens, etc. In the process of electron transfer, the use of redox mediator for the electron transfer between the cell and the electrode is called electron shuttle mechanism. According to the source of redox mediator, it can be divided into exogenous redox mediator and endogenous redox mediator (cell autocrine). So far, little was known about the potential of Bacillus cereus to produce electricity.In this work, an efficient phenol-degrading electricigenic bacterium was separated and screened, and its MFC was built using the obtained strain, and the efficiencies of phenol degradation and electricity production were further investigated. Meanwhile, the anode carbon felt was analyzed by scanning electron microscopy, and the cyclic voltammetry curve of the obtained strain was measured during the four growth stages (7, 18, 31 and 52 h), to explore the potential related mechanism of electricity production.Twenty-one pure strains with potential ability of electricity production were isolated, of which WL013, WL024 and WL027 strains could produce electricity, and the WL027 was the favorite electricity-producing strain. Hence, the strain WL027 was selected as the dominant strain. Based on the combination results of 16S rDNA and physiological and biochemical characteristics, the strain WL027 was identified as Bacillus cereus. This strain WL027 was electrochemically active, and its electricity was mainly generated at the stable phase during the growth of the strain. When the strain WL027 was inoculated into the MFC, the maximum voltage increased by 179 mV compared with the start voltage, with Coulombic efficiency of 64.25% and phenol degradation rate of 68.62%. The intracellular and extracellular concentrations of riboflavin were 6.10×10-3 and 1.32×10-2 mg/L respectively during the process of electricity production. The voltage was increased by 18 mV when the riboflavin was added to the MFC at the stable phase. Therefore, it can be speculated that the strain WL027 could promote the electron transport through the secretion of riboflavin in microorganisms.In conclusion, the MFC constructed by Bacillus cereus not only can degrade phenol efficiently, but also has obvious advantages in energy conversion efficiency. Besides, the strain WL027 can promote the electron transport through the secretion of riboflavin in microorganisms.